PENERAPAN STRATEGI MEMBACA INTERAKTIF DALAM PEMBELAJARAN BAHASA INDONESIA UNTUK MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS 3 SEKOLAH DASAR - Awaliyah, Khoiru Nisa; Ismiyanti, Yulina; Yustiana, Sari (STKIP Persada Khatulistiwa Sintang, 2025)
Reading is a vital skill in Indonesian language learning that requires comprehension, analysis, and active engagement. Therefore, reading strategies play a crucial role in making the reading process more effective. This study aims to explain the implementation of interactive reading strategies in Indonesian language instruction to develop the critical thinking skills of third-grade elementary school students. The research employs a qualitative approach with a case study design. Data collection techniques include observation, questionnaires, and documentation. The data were analyzed by identifying patterns related to the research objectives. Data triangulation was carried out through sources, theories, researchers, techniques or methods, and time. The implementation of interactive reading strategies in Indonesian language learning has shown a positive impact on the development of students’ critical thinking skills. Through well-prepared planning, organized implementation, and structured evaluation, this strategy increases student engagement in reading and discussion. Indicators of critical thinking developed among students include the ability to ask critical questions, provide reasoning, and draw conclusions, demonstrating that the strategy effectively enhances critical thinking skills. Although there were some inhibiting factors, such as limited time and varying student abilities, supporting factors like teacher involvement and student collaboration helped address these challenges.